[Crowd at Farmers' Institute Picnic] - Frank Aston::::::photographer::: (1915)
Crowd at the Farmers' Institute (Farmers' Picnic); watching procession of draft horses and cattle. 'no. 17' in lower right corner; image from same event appears in March 1915 Bulletin (Series II, No. 2)